Rumen fermentation characteristics, ciliate protozoa and utilization of nutrients in sheep fed sodium hydroxide treated mustard straw - MISHRA, A S; SANTRA, A; CHATURVEDI, O H; MISRA, A K; PRASAD, R; JAKHMOLA, R C (The Indian Journal of Animal Sciences, 2014)
Mustard straw (MS) was treated with sodium hydroxide (2% w/v) by soaking (6 hr) method. Mulpurn rams (8) were divided into 2 groups. One grcup (G1) was offered untreated MS (UMS) ad lib. along with concentrate (1% common salt) @ 250 g /head/day, and group (G2) was offered (reated MS (TMS) ad lib. along with concentrate (without common salt) @ 250 g /head/day. Daily intakes of DM and OM between groups did not differ signiflcantly. However. rams in G2 consumed 12% higher amount of straw. The rumen pH increased and TVFA (meg/dl SRL) decreased in G2 as compared to G1. However, the concentration (mg/dl SRL) oftotal-N, Nll3-N and TCA-N was similar in G2 and G1. The population (X 104/ml SRL) of spirotrichs was lower in G 1 than that in G2 while of holotrichs higher in G1 than that in G2. Digestibility coefficients ofDM, OM, NDF, ADF and cellulose were higher in G2 than that in Gland the respective means were 45.8 and 52.9, 51.3 and 58, 38.1 and 47, 31.4 and 39.6 and 36.8 and 54.0. However, CP, hemicellulose and gross energy digestibility did not show much variation. Rams in both the groups were Oil positive N balance and N retention (% of N intake) was 37.7 and 47.1 in Gland 02 respectively. The DCP (%) of the ration was higher in Gl (7.0) than that in (12(5.6), whereas DE (Mcal/kg) of the ration did not differ significantly in G1 (2.4) and G2 (2.5). It is concluded that on feeding of sodium hydroxide treated mustard straw-based ration, the number of holotriehs protozoa decreascd while spirotrichs increased in the rumen of sheep. The soaking of mustard straw in 2% sodium hydroxide solution for 6 hr improved its palatability and digestibility and thus feeding value.